Images of the Twenty-First Century. Proceedings of the Annual International Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.1989.95743
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and circadian temperature rhythms in winter depression

Abstract: Winter depression is associated with a phase-delay of the temperature rhythm in a constant routine. Bright morning light treats the depression and phase advances the temperature rhythm. There is a need for a s~l l inexpensive temperature monitoring device to diagnose and treat circadian rhythm problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Phase delays have been reported in patients with winter depression compared with controls in some studies, 9,33,41 but not in others, 42 and no study has reported a phase advance. However, an ipsative phase delay (ie, a delay in patients when depressed in the winter compared with when they are euthymic in the summer) 10 has not always been found.…”
Section: Commentmentioning
confidence: 92%
“…Phase delays have been reported in patients with winter depression compared with controls in some studies, 9,33,41 but not in others, 42 and no study has reported a phase advance. However, an ipsative phase delay (ie, a delay in patients when depressed in the winter compared with when they are euthymic in the summer) 10 has not always been found.…”
Section: Commentmentioning
confidence: 92%